2019
DOI: 10.1002/cncr.32611
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHA5 regulates tumor growth in metastatic melanoma

Abstract: Background PLEKHA5 has previously been identified as a novel molecule implicated in melanoma brain metastasis, a disease that continues to portend a poor prognosis. The aim of this study was to further investigate the functional role of PLEKHA5 in disseminated melanoma. Methods The impact of PLEKHA5 on proliferation and tumor growth was examined in vitro and in melanoma xenograft models, including brain‐tropic melanomas (melanomas tending to disseminate to the brain). In vitro loss‐ and gain‐of‐function studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(129 reference statements)
0
18
1
Order By: Relevance
“…We previously established Pleckstrin Homology Domain Containing A5 ( PLEKHA5 ), a gene involved in normal brain development, as a regulator of melanoma growth in brain metastasis [ 22 ]. Our data suggested that PLEKHA5-mediated growth could be attributed to its role in regulating the cell cycle inhibitor, programmed cell death 4 (PDCD4), via crosstalk with the ubiquitin-proteasome and phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) signaling pathways critical in PDCD4 complex regulation [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Our study of paired cranial and extracranial human melanomas showed that high PDCD4 expression in cerebral specimens is significantly associated with improved survival, suggesting a role for PDCD4 loss in dysregulating melanoma brain metastasis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously established Pleckstrin Homology Domain Containing A5 ( PLEKHA5 ), a gene involved in normal brain development, as a regulator of melanoma growth in brain metastasis [ 22 ]. Our data suggested that PLEKHA5-mediated growth could be attributed to its role in regulating the cell cycle inhibitor, programmed cell death 4 (PDCD4), via crosstalk with the ubiquitin-proteasome and phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) signaling pathways critical in PDCD4 complex regulation [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Our study of paired cranial and extracranial human melanomas showed that high PDCD4 expression in cerebral specimens is significantly associated with improved survival, suggesting a role for PDCD4 loss in dysregulating melanoma brain metastasis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a small cohort of primary melanomas, low cellular PDCD4 mRNA levels correlated with increased tumor size, high Clark level, and lymph node metastases [ 30 ]. Our group reported prognostic significance of total PDCD4 protein levels (cytoplasmic and nuclear) by quantitative immunofluorescence (QIF) in a small cohort of melanoma metastases and shorter survival among patients with absent or low levels of PDCD4 in cerebral lesions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PLEKHA5 is also been found to abundantly expressed in the cytoplasm and cell membrane, and closely related to the process of cell migration and vascular formation [27] . In the cell model of brain metastasis of melanoma, knockdown of PLEKHA5 inhibits the proliferation of tumor cells, blocks cell cycle at G1-S progression, thereby inhibiting the tumorigenesis of tumor cells in vivo [28] . CircRNAs is a class of endogenous RNA with an atypical structure of covalently binding of 5'-and 3'-ends.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the PH domain that PLEKHA5 contains, PLEKHA5 was supposedly to be associated with multiple phosphoinositide binding properties and PI3K-AKT pathway, thereby participating in intracellular functions [44] . It was reported that the expression of phosphorylated AKT (p-Akt) was decreased in PLEKHA5-depleted melanoma cells [28] . By scanning the amino acid sequence, PH domain was also found in circ-PLEKHA5-622aa.…”
Section: Discussionmentioning
confidence: 99%